The impact of automated hippocampal volumetry on diagnostic confidence in patients with suspected Alzheimer's disease: A European Alzheimer's Disease Consortium study. Issue 9 (3rd March 2017) - Bosco, Paolo; Redolfi, Alberto; Bocchetta, Martina; Ferrari, Clarissa; Mega, Anna; Galluzzi, Samantha; Austin, Mark; Chincarini, Andrea; Collins, D. Louis; Duchesne, Simon; Maréchal, Bénédicte; Roche, Alexis; et al.
Abstract: Introduction: Hippocampal volume is a core biomarker of Alzheimer's disease (AD). However, its contribution over the standard diagnostic workup is unclear. Methods: Three hundred fifty‐six patients, under clinical evaluation for cognitive impairment, with suspected AD and Mini–Mental State Examination ≥20, were recruited across 17 European memory clinics. After the traditional diagnostic workup, diagnostic confidence of AD pathology (DCAD) was estimated by the physicians in charge. The latter were provided with the results of automated hippocampal volumetry in standardized format and DCAD was reassessed. Results: An increment of one interquartile range in hippocampal volume was associated with a mean change of DCAD of −8.0% (95% credible interval: [−11.5, −5.0]). Automated hippocampal volumetry showed a statistically significant impact on DCAD beyond the contributions of neuropsychology, 18 F‐fluorodeoxyglucose positron emission tomography/single‐photon emission computed tomography, and cerebrospinal fluid markers (−8.5, CrI: [−11.5, −5.6]; −14.1, CrI: [−19.3, −8.8]; −10.6, CrI: [−14.6, −6.1], respectively). Discussion: There is a measurable effect of hippocampal volume on DCAD even when used on top of the traditional diagnostic workup.